2020
DOI: 10.21203/rs.2.24059/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The effectiveness of application of the standardized terminology for telephone follow-up model in discharge follow-up of patients with cancer pain.

Abstract: Purpose This article aims to explore a standardized telephone follow-up model for patients with cancer pain, thus to promote standardized management of discharge follow-up of the patients with cancer pain.Method We have developed a flow chart of standard terminology for discharge follow-up of the patients with cancer pain. The 80 patients with cancer pain who have discharged from our hospital were divided into the control group (40 cases) and the observation group (40 cases), both groups were followed up by te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The study included 1400 and 1172 participants in the intervention and control groups, respectively. Ten studies [12][13][14][15][16][17][18][19][20][21][22][23] reported on the duration of indwelling PICC, six [24][25][26][27][28][29] on health-promoting lifestyle pro les (HPLP), and three [30][31][32] on quality of life.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The study included 1400 and 1172 participants in the intervention and control groups, respectively. Ten studies [12][13][14][15][16][17][18][19][20][21][22][23] reported on the duration of indwelling PICC, six [24][25][26][27][28][29] on health-promoting lifestyle pro les (HPLP), and three [30][31][32] on quality of life.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…This meta-analysis found that continuity of care signi cantly improved patients' healthy lives compared to conventional follow-up in 1020 individuals across six trials [24][25][26][27][28][29]. Health-promoting behaviors give individuals greater control over their health and its determinants, allowing them to improve their health.…”
Section: Out-of-hospital Continuity Of Nursing Care Can Improve Patie...mentioning
confidence: 99%